Work and Labour Relations in Global Platform Capitalism - Haidar, Julieta; Keune, Maarten (ILERA Publication series, 2021)
This engaging and timely book provides an in-depth analysis of work and labour relations within global platform capitalism with a specific focus on digital platforms that organise labour processes, known as labour platforms. Well-respected contributors thoroughly examine both online and offline platforms, their distinct differences and the important roles they play for both large transnational companies and those with a smaller global reach.